MicroRNA‐493 is a prognostic factor in triple‐negative breast cancer. Issue 7 (27th June 2018) - Yao, Ling; Liu, Yirong; Cao, Zhigang; Li, Junjing; Huang, Yanni; Hu, Xin; Shao, Zhiming
Abstract : Breast cancer is one of the most common malignant diseases in women. Triple‐negative breast cancer (TNBC) shows higher aggressiveness and recurrence rates than other subtypes, and there are no effective targets or tailored treatments for TNBC patients. Thus, finding effective prognostic markers for TNBC could help clinicians in their ability to care for their patients. We used tissue microarrays (TMAs) to detect microRNA‐493 (miR‐493) expression in breast cancer samples. A miRCURY LNA detection probe specific for miR‐493 was used in in situ hybridization assays. Staining results were reviewed by two independent pathologists and classified as high or low expression of miR‐493. Kaplan–Meier survival plots and multivariate Cox analysis were carried out to clarify the relationship between miR‐493 and survival. In the Kaplan–Meier analysis, patients with high miR‐493 expression had better disease‐free survival than patients with low miR‐493 expression. After adjusting for common clinicopathological factors in breast cancer, the expression level of miR‐493 was still a significant prognostic factor in breast cancer. Further subtype analysis revealed that miR‐493 expression levels were only significantly prognostic in TNBC patients. These results were validated in the Molecular Taxonomy of Breast Cancer International Consortium database for overall survival. We proved the prognostic role of miR‐493 in TNBC by using one of the largest breast cancer TMAs available and validated it in a large public RNA sequencing database. Abstract : In Kaplan–Meier analysis, patients with high miR‐493 expression had better disease‐free survival than patients with low miR‐493 expression. Further subtype analysis revealed that miR‐493 expression levelswereonly significantly prognostic in TNBC patients.